Pengaruh Kelas Pre-Natal Terhadap Kadar Hemoglobin Ibu Hamil Di Wilayah Kerja Puskesmas Kartasura Kabupaten Sukoharjo - Puspita Sari, Risky; , Vinami Yulian,Ns., M.Sc. Nursing (2016)
The hemoglobin level is a biochemical indicator to determine the nutritional status of pregnant women. The amount of hemoglobin in the blood is approximately 15 grams per 100 ml of blood. The normal value Hb of pregnant women is 12.5 to 15.5 g / dL or g / 100 ml.This study aims to determine the influence of the pre-natal to hemoglobin levels of pregnant women in Puskesmas Kartasura Sukoharjo Researchers used quantitative research and methods of pre-experimental design with one group pretest-posttest control group study was conducted in Puskesmas Kartasura Sukoharjo district. When the study in April-May 2016. The study population was all pregnant women in Puskesmas Kartasura Sukoharjo district in November 2015 with a population of 136 people. The sample used in this study were 58 respondents. Instruments used in the study is a sheet of identity and a set of hemoglobin. The study consisted of two groups: the treatment group and the control group with the results of pre-post test.Data analysis techniques used in this study paired sample test. The results showed no difference between pre and post the hemoglobin levels in the control group that is equal to p (0.561) <0.05. there is a difference between the pre danpos on hemoglobin levels of pregnant women that is equal to the control group p (0013)> 0.05. Keywords: prenatal. Hemoglobin levels.pregnantmothe